Global Image Through Local Cuisine: Exploring Culinary Diversity In Global Tourism - Julian Andriani Putri; Tuwuh Adhistyo Wijoyo (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Over the past few decades, the global tourism industry has seen significant growth, leading to an increased demand for culturally immersive travel experiences. This study the importance of food in modern tourism, where it serves not only as a basic necessity but also as a vital tool for experiencing and understanding local cultures. Local cuisine, often referred to as "local flavor," has become a central attraction in the tourism industry due to its embodiment of unique creativity, cultural heritage, and the values of indigenous communities. Local food also has the potential to promote cultural diversity in the era of globalization. This research investigate the various challenges faced by local cuisine in the context of global tourism, including the preservation of food authenticity while catering to the preferences of global travelers. It will also explore the role of local food in shaping perceptions of tourist destinations, examining how the tourism industry influences people's views of local cuisine and its role in facilitating an understanding of local culture. Striking a balance between maintaining the authenticity of local food and meeting tourists' expectations is a complex challenge to be discussed in this study. The findings of this research have the potential to offer valuable insights into the impact of local cuisine on the tourism sector, the image of local food, business opportunities, and cultural influence. It is expected that these research findings contribute to the development of strategies aimed at promoting local culinary traditions, preserving cultural sustainability, and enhancing truly authentic tourism experiences.